If Cos (theta) = (frac{12}{13}). Find (theta) + cos

^{2}(theta)-
**A.**

(frac{169}{25}) -
**B.**

(frac{25}{169}) -
**C.**

(frac{169}{144}) -
**D.**

(frac{144}{169})

##### Correct Answer: Option A

##### Explanation

Cos (theta) = (frac{12}{13})

x^{2} + 12^{2} = 13^{2}

x^{2} = 169- 144 = 25

x = 25

= 5

Hence, tan(theta) = (frac{5}{12}) and cos(theta) = (frac{12}{13})

If cos^{2}(theta) = 1 + (frac{1}{tan^2theta})

= 1 + (frac{1}{frac{(5)^2}{12}})

= 1 + (frac{1}{frac{25}{144}})

= 1 + (frac{144}{25})

= (frac{25 + 144}{25})

= (frac{169}{25})